Hearing Impairment and its Reflection in Psychological Diagnostics - Potmesilova, Petra; Potmesil, Milon; Bełza, Magdalena (Wydawnictwo Naukowe UAM, 2016)
The authors hereby present a report on research aimed at the possibilities of adjustments of psychodiagnostic materials to be used in the population of children with hearing impairments in order to reduce or eliminate the functional impact of the defect on the child's performance and consequently on the diagnostic process. The adjustment was made by formal language modification without intervention in the content, and by the creation of a version in Czech sign language. The B4J.E.P.I. personality questionnaire and a comprehension subtest using the Wechsler intelligence scale for children (further WISC4III) were experimentally modified and tested in practice between 2011 and 2016.
Upośledzenie słuchu i jego odzwierciedlenie w diagnostyce psychologicznej
Keywords: hearing impairment; psychological diagnostics; psychosocial context of hearing impairment